Reaksi Pasar Atas Right Issue - Firstiany, Jacqueline Immanuele; Wirama, Dewa Gede (E-Jurnal Akuntansi; Vol 27 No 1 (2019), 2019)
Right issue is one of corporate actions that can affect the number and price of shares in the market. The information content from the announcement of the rights issue becomes important, because it can make the market react to the announcement. This study aims to examine the information content of the announcement of the rights issue at the Indonesia Stock Exchange with a research period of 10 years, from 2008 to 2017. Testing the information content of an event such as the announcement of the rights issue generally uses event study. The event window used in this study is 5 days using market-adjusted model in calculating abnormal returns. The sample of this study is 146 companies which were determined by purposive sampling method. Different from those hypothesized, the results of the one sample t-test indicates that the market does not react to the announcement of rights issue. Keywords: Right issue, market reaction, event study, market-adjusted model, abnormal return